Role of pre-procedure CCTA in predicting failed percutaneous coronary intervention for chronic total occlusions - Hua Zhou; Xiaojun Fan; Mingyuan Yuan; Wei Wang; Qiyuan Wu (European Journal of Radiology Open, 2024)
Purpose: This study aimed to identify major lesion characteristics of chronic total occlusions (CTOs) that predict failed percutaneous coronary intervention (PCI) using pre-procedure coronary computed tomography angiography (CCTA) in combination with conventional coronary angiography (CCA). Methods: Consecutive patients with at least one CTO of the native coronary arteries received CCTA and CCA-guided PCI, with computed tomography performed before or during PCI. Results: A total of 76 patients with CTO were included in this study. 76 patients were divided into successful and failed PCI groups based on their PCI outcome. There were 62 (81.58 %) patients in the successful PCI group and 14 (18.42 %) in the failed PCI group. The occlusion length ≥20 mm, ostial or bifurcation lesions, negative remodeling, microchannels, and good collateral vessels were the CCTA morphologic parameters associated with PCI outcome (P<0.05). In addition, the blunt stump, occlusion length ≥20 mm, and ostial or bifurcation lesions, were the CCA morphologic parameters associated with PCI outcome (P<0.05). The multivariate regression model showed that the three independent negative predictors: blunt stump on CCA (OR: 0.63; 95 % CI: 0.23–0.98; p =0.048), occlusion length ≥20 mm on CCTA (OR: 0.37; 95 % CI: 0.32–0.71; p <0.001) and negative remodeling on CCTA (OR: 0.26; 95 % CI: 0.28–0.44; p <0.001). Conclusion: Our study demonstrated that combining CCTA and CCA morphologic characteristics could improve PCI outcome prediction in patients with CTO compared to CCTA morphologic features alone.